Quality and vigor of barley cv. Brennus seeds - Domínguez-Martínez, Pablo Alfredo; Alejos - de la Fuente, José Isidro; Vaquera-Huerta, Humberto; Pro-Martínez, Arturo; Hernández, Glafiro; Mendoza-Pedroza, Sergio Iban; Villarreal-González, Jorge Armando (Ecosistemas y Recursos Agropecuarios, 2025)
Barley in Mexico is an important crop for the brewing industry and animal feed. The physical and physiological quality and vigor of a batch of seed cv. Brennus was evaluated. The seed was divided by size (small and large) with a 2.5 mm sieve and subjected to different conditioning (aging and non-aging). The study variables were seed purity (SP), thousand seed weight (P1000S), volumetric weight (PV), moisture content (H), germination percentage, emergence speed, plumule length, dry matter in the plumule and seedling vigor index. The analysis of variance was performed under a completely randomized experimental design with factorial arrangement and four replications. Means were compared using Tukey’s test (P < 0.05). The lot presented 98% SP, 1.8% inert material and 0.2% other seeds, P1000S was 42 g, PV 68 kg hL-1 and H was 7%. There were statistical differences (P < 0.05) between seed size, seed conditioning and interaction of both factors for most variables. Small and large unaged seeds showed similarity in germination, emergence speed, plumule length and seedling vigor index. The aging treatment had a negative effect on these variables regardless of size; however, the most extensive damage was seen on the large seeds. The seed lot has poor physical and physiological quality and vigor.